2016 Power Systems Computation Conference (PSCC) 2016
DOI: 10.1109/pscc.2016.7540885
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated corrective control for transient stability enhancement in future Great Britain transmission system

Abstract: Abstract-This paper demonstrates a corrective control strategy through fast actuators (TCSC FACTS and HVDC links, both LCC and VSC) in order to enhance the transient stability in the future Great Britain (GB) transmission network. A model predictive control (MPC) scheme that relies on system wide-area measurements is employed for coordinated control action through these power electronic devices with the aim of preserving the system stability without having to constrain prefault transfer levels. Case studies em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The deviation of the generator rotor speeds from this value (relative frequency error) was found to provide good performance in [13], [8]. Finally, it is important to highlight in (2e) the constraints on the control variable u(k) according to the short-term overload capabilities of the HVDC converter.…”
Section: B Mpc-based Podmentioning
confidence: 99%
See 2 more Smart Citations
“…The deviation of the generator rotor speeds from this value (relative frequency error) was found to provide good performance in [13], [8]. Finally, it is important to highlight in (2e) the constraints on the control variable u(k) according to the short-term overload capabilities of the HVDC converter.…”
Section: B Mpc-based Podmentioning
confidence: 99%
“…Although use of VSC-HVDC links for damping support has been extensively covered in the literature, it is often assumed that the converter is operating de-loaded [7], [8] (which can be economically expensive) or that some overload is available without addressing the converter physical limitations [9], [10]. In order to explicitly account for the converter overload constraints in the controller design in this work we use model predictive control (MPC) theory [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control implementation relies on relative frequency error between generators and AC grid. An MPC-based transient stability controller for the representative GB system is proposed as well in [78]. However, the feasibility of implementing such control in the real power system is yet to be assessed since the designing of MPC for large systems is non-trivial.…”
Section: Large-disturbance Angle Stabilitymentioning
confidence: 99%
“…MPC has been shown to offer setpoint tracking and robustness performance in a range of power systems applications including secondary frequency control, typically referred to as automatic generation control (AGC) [9]- [11], and voltage control [12], [13]. Additionally, MPC has been suggested for application to the dynamic control of point-to-point HVDC links [14], [15] and for providing predictive optimal power flow for MTDC systems in [16]. Recently it was shown that MPC could be used as a means of improving AGC performance and robustness for ac areas connected to MTDC grids versus decentralised PI based techniques [11], [17].…”
Section: Introductionmentioning
confidence: 99%